1999
DOI: 10.1128/mcb.19.4.2880
|View full text |Cite
|
Sign up to set email alerts
|

Functional Domains of c-myc Promoter Binding Protein 1 Involved in Transcriptional Repression and Cell Growth Regulation

Abstract: c-myc promoter binding protein 1 (MBP-1), initially identified from a human cervical carcinoma (HeLa) cell expression library, binds to the TATA box sequences of the c-myc P2 promoter and negatively regulates both human and mouse c-myc promoter activities (6,25,26). The c-myc proto-oncogene can promote cell proliferation, differentiation, and oncogenic transformation (7,36) or apoptosis under certain conditions (9, 35). Regulation of c-myc occurs at multiple levels, such as the initiation or termination of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 38 publications
1
47
0
Order By: Relevance
“…CMVGFP-MEK5␤ fusion construct, a gift from J.-I. Abe (University of Rochester Medical Center, Rochester, NY), and CMV MBP-1 (14) were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CMVGFP-MEK5␤ fusion construct, a gift from J.-I. Abe (University of Rochester Medical Center, Rochester, NY), and CMV MBP-1 (14) were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…MBP-1, ubiquitously expressed in different human tissues (9), is located at human chromosome 1p35-pter (10). MBP-1, an ϳ37-kDa cellular protein, has many intriguing properties such as transcriptional repressor activity, induction of apoptosis, and regression of tumor growth (8,(11)(12)(13)(14)(15). Sequence analysis suggests that MBP-1 has a high homology with Eno1 cDNA (8), designated as human ␣-enolase cDNA (16).…”
mentioning
confidence: 99%
“…It was demonstrated that the expression levels of ING3 are decreased in melanoma and head and neck squamous cell carcinoma, and predict a poor prognosis (34). DENND4A, also known as C-myc promoter-binding protein MBP-1, acts as a general transcriptional repressor (35). It binds to c-myc promoter sequences and transcriptionally represses the c-myc gene (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…NPM/ B23 and enolase-α), which play such different functional roles in the cell, interrelate in the promitogenic/prosurvival bystander response? It has been reported that enolase-α also plays an important role in the regulation of c-myc promoter activity in the form of alternative translation product MBP-1 (37-40 kDa), which is distinct from its role as a glycolytic enzyme [59][60][61][62]. The c-myc proto-oncogene is known as an essential part of normal cell proliferative machinery [63,64].…”
Section: Cooperation Of Npm and Enolase-α In Pbrmentioning
confidence: 99%
“…The c-myc proto-oncogene is known as an essential part of normal cell proliferative machinery [63,64]. MPB-1, structurally very similar to enolase-α, binds to the c-myc P2 promoter and down-regulates c-myc expression, and therefore, suppresses cell proliferation [60][61][62]. Unlike enolase-α, which is mainly localized in the cytoplasm, MPB-1 has been primarily found in the cell nuclei [61].…”
Section: Cooperation Of Npm and Enolase-α In Pbrmentioning
confidence: 99%